2016
DOI: 10.1186/s13613-016-0173-1
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of platelets, but not of red blood cells, is independently associated with nosocomial infections in the critically ill

Abstract: BackgroundRed blood cell (RBC) transfusion has been associated with nosocomial infection in the critically ill patients. However, this association may be confounded by length of stay, as prolonged intensive care unit (ICU stay) increases both risk of infection and risk of transfusion. Also, it is not known whether specific blood products have differential risks.MethodsIn this prospective multicentre cohort study, the risk of bacterial infections associated with transfusion products in critically ill (ICU) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 24 publications
0
39
0
2
Order By: Relevance
“…Beyond hemostasis, PLTs are complex and may also mediate immune and inflammatory effects and have been associated with thrombosis and infection to which certain populations may be more susceptible. In the PATCH trial, which randomized 190 patients with intracranial hemorrhage on anti‐PLT medications to receive or not receive PLT transfusions, functional outcomes were worse in the transfused group, and in an observational ICU study, PLT transfusions were found to be an independent predictor of venous thromboembolism (HR, 3.2; 95% CI, 1.2‐8.4) .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond hemostasis, PLTs are complex and may also mediate immune and inflammatory effects and have been associated with thrombosis and infection to which certain populations may be more susceptible. In the PATCH trial, which randomized 190 patients with intracranial hemorrhage on anti‐PLT medications to receive or not receive PLT transfusions, functional outcomes were worse in the transfused group, and in an observational ICU study, PLT transfusions were found to be an independent predictor of venous thromboembolism (HR, 3.2; 95% CI, 1.2‐8.4) .…”
Section: Discussionmentioning
confidence: 99%
“…A limited range in possible storage time will automatically limit the differences. In several studies an association between PLT transfusions and risk of all‐cause infection has been reported . However, confounding by indication could be a potential explanation for these findings, since patients receiving PLT transfusions are at an inherently different risk of infection than those not receiving PLT transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies an association between PLT transfusions and risk of all-cause infection has been reported. [28][29][30] However, confounding by indication could be a potential explanation for these findings, since patients receiving PLT transfusions are at an inherently different risk of infection than those not receiving PLT transfusions. We investigated differences in storage time, since PLT products are released on a first-in-first-out basis, without consideration of the patients' prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies to date have failed to sufficiently characterize or account for individual differences in pretransfusion immune function. Additionally, patients who are transfused with RBCs often also receive other blood products, which may have different or additive TRIM effects . Overall, much work remains to understand interactions between individual blood product characteristics and patient‐specific risk factors with respect to clinical consequences of TRIM.…”
Section: Future Directionsmentioning
confidence: 99%